2018
DOI: 10.2134/jeq2017.07.0284
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanoparticle Surface Properties on the Attachment of Cerium Oxide Nanoparticles to Sand and Kaolin

Abstract: Soil texture has been found to be a critical factor in regulating the fate and transport of cerium oxide nanoparticles (CeONPs) in the terrestrial environment. However, the underlying mechanisms for the interactions between CeONPs and different components of soil are still poorly understood. The attachment of CeONPs onto two typical components of soil (sand and kaolin) in batch experiments were investigated to provide insights into the retention and bioavailability of CeONPs in soil. Surface properties of CeON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Wang et al showed that the transport of CdSe/ZnS or CdSe/CdZnS QDs in sand is primarily governed by the surface charge of the particle rather than the molecular weight of the ligand or the overall particle size (Wang et al, 2013). Surface modified ENMs with negative zeta (ζ) potential have been shown to be more mobile in sand compared to positively charged or neutral particles (Wang et al, 2013;Zhang et al, 2018), thereby increasing bioavailability and in planta translocation to aerial tissues (Judy et al, 2012;Zhu et al, 2012;Spielman-Sun et al, 2017;Ashfaq et al, 2017;Al-Salim et al, 2011;Koo et al, 2015). It is important to understand the mechanisms controlling ENM bioavailability, localization, and accumulation, as well as associated impacts on plant and soil health, as influenced by surface coating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al showed that the transport of CdSe/ZnS or CdSe/CdZnS QDs in sand is primarily governed by the surface charge of the particle rather than the molecular weight of the ligand or the overall particle size (Wang et al, 2013). Surface modified ENMs with negative zeta (ζ) potential have been shown to be more mobile in sand compared to positively charged or neutral particles (Wang et al, 2013;Zhang et al, 2018), thereby increasing bioavailability and in planta translocation to aerial tissues (Judy et al, 2012;Zhu et al, 2012;Spielman-Sun et al, 2017;Ashfaq et al, 2017;Al-Salim et al, 2011;Koo et al, 2015). It is important to understand the mechanisms controlling ENM bioavailability, localization, and accumulation, as well as associated impacts on plant and soil health, as influenced by surface coating.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the mechanisms controlling ENM bioavailability, localization, and accumulation, as well as associated impacts on plant and soil health, as influenced by surface coating. Several researchers have investigated the uptake of differentially coated QDs (Koo et al, 2015;Li et al, 2018), metal-based (Zhang et al, 2018;Judy et al, 2012;Zhu et al, 2012;Spielman-Sun et al, 2017;Li et al, 2016), and carbon-based (Ashfaq et al, 2017) nanomaterials by plants. Among ENMs, QDs are the least studied in agricultural crops, thus demanding immediate attention.…”
Section: Introductionmentioning
confidence: 99%
“… 64 nZVI has small particle size and high surface energy, which can adsorb heavy metals or cationic pollutants easily, but it is very difficult to separate it from either sludge or effluent. 65 Coating Pd on nZVI surfaces has improved the interstitial characteristics of nZVI; 66 the co-existing organic and inorganic substances impact each of the modified/immobilized nZVI–composites via various mechanisms and reduce the targetted heavy metals removal action from the solution. Hence, modifying the nZVI via additional support material to improve the effect of co-existing interfering substances is helpful.…”
Section: Heavy Metal (Pb CD and Cu) Removal Efficiency Of Nzvimentioning
confidence: 99%
“…Binding of positively charged uncoated CeO 2 nanoparticles to these negative charged sites, which will be abundant in the clayey loam LUFA Speyer 2.4 (Supporting Information SI 7), could prevent dissociation of CeO 2 within the worms upon ingestion. Indeed, investigation into the adsorption of CeO 2 nanoparticles of similar size to those studied in this article (<25 nm) in model saturated soils, demonstrated greater attachment of the nanomaterials to kaolin clay than sand particles in batch experiments (Zhang et al 2018). Positively charged CeO 2 also had greater attachment to kaolin clays than negatively charged forms, attributed to physical adsorption processes through electrostatic interactions.…”
Section: The Role Of Size and Dissolution On Bioaccumulation Of Cerium From Sedimentsmentioning
confidence: 51%